2022
DOI: 10.1101/2022.01.11.475964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic diversity and population structure of sweet orange [Citrus sinensis (L.) Osbeck] germplasm of India revealed by SSR and InDel markers

Abstract: Sweet orange (Citrus sinensis (L.) Osbeck) is an important commercial citrus fruit crop, cultivated in India and across the world. In India most of the cultivated sweet orange species were introduced varieties. In this study, we used two molecular markers, SSR and InDels, to understand the genetic diversity and population structure of seventy-two sweet orange genotypes. Genetic parameters consisted of a total number of alleles, a number of polymorphic alleles (effective alleles); genetic diversity (G.D.), expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Group VII included Eureka lime (hybrid between C. aurantium × C. medica) and Rangpur lime (hybrid between C. reticulata × C. medica) with a dissimilarity index of 0.759, which showed closer genetic relationships with acid limes and a high genetic differentiation with the rest of the citrus populations. These results agree with those obtained by Nicolosi et al (2000) and Kumar et al (2022), who found close phylogenetic relationships between C. medica, C. aurantifolia, and C. limon. The PCoA principal coordinate analysis in the first three coordinates explained 62.44 % of the total variability of the 19 citrus populations (Figure 2).…”
Section: Genetic Distancesupporting
confidence: 93%
“…Group VII included Eureka lime (hybrid between C. aurantium × C. medica) and Rangpur lime (hybrid between C. reticulata × C. medica) with a dissimilarity index of 0.759, which showed closer genetic relationships with acid limes and a high genetic differentiation with the rest of the citrus populations. These results agree with those obtained by Nicolosi et al (2000) and Kumar et al (2022), who found close phylogenetic relationships between C. medica, C. aurantifolia, and C. limon. The PCoA principal coordinate analysis in the first three coordinates explained 62.44 % of the total variability of the 19 citrus populations (Figure 2).…”
Section: Genetic Distancesupporting
confidence: 93%
“…One of Indonesia's leading horticultural commodities is fruit, and Indonesia has local superior citrus species and varieties that are spread throughout the archipelago. Citrus is one of the world's major fruit crops [3], grown in many regions [4], which has high economic value [5]. Citrus fruits belong to the family Rutaceae and subfamily Aurantioideae and can be grown in tropical and sub-tropical climates [6].…”
Section: Introductionmentioning
confidence: 99%